2017
DOI: 10.1155/2017/7302892
|View full text |Cite
|
Sign up to set email alerts
|

Focal Muscle Vibration and Physical Exercise in Postmastectomy Recovery: An Explorative Study

Abstract: Background. Physical activity initiation and maintenance are particular challenges in the postmastectomy recovery and in particular Dragon Boat racing seems to be a useful sport activity. The aim of this study was to evaluate the role of focal muscle vibration as a proprioceptive input to improve upper limb functioning in a group of “paddlers” patients. Methods. A group of paddlers has been evaluated before vibratory treatment (T0), immediately after therapy (T1), after one week (T2), and after one month (T3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…In this regard, MVC increased up to ≈+30% in young subjects [35], whereas, in the elderly, MVC improvements of ≈+40% and ≈+50% were reported, respectively, in males and females [33]. It is noticeable that another study, not included since the evaluation was performed only immediately after the end of FVT [42], supported the MVC increase reported in a previous study by the same authors [23]. Only in a single study did MVC not increase, even if the rate of the force development (RFD) improved (≈+27%) [30].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this regard, MVC increased up to ≈+30% in young subjects [35], whereas, in the elderly, MVC improvements of ≈+40% and ≈+50% were reported, respectively, in males and females [33]. It is noticeable that another study, not included since the evaluation was performed only immediately after the end of FVT [42], supported the MVC increase reported in a previous study by the same authors [23]. Only in a single study did MVC not increase, even if the rate of the force development (RFD) improved (≈+27%) [30].…”
Section: Discussionsupporting
confidence: 83%
“…The muscle state may be contracted or relaxed during stimulation. The tested performance parameters are different, belonging to several physiological functionalities, from the simple force amplitude to the force time course or movement coordination, with outcome follow-ups ranging from hours to months [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Such protocol differences are likely the origin of different reported results.…”
Section: Introductionmentioning
confidence: 99%
“… 21 23 Although there is no universal consensus on the ideal protocol, the transmission of high- and low-intensity mechanical signals simulates the physiological stimuli that the human body encounters in daily life, ensuring safer effects than those of mild training programs. 50 , 51 Several groups have shown that mFV consistently alters the interaction between the vibrated muscle and its antagonists and increases motor coordination, thus likely improving joint performance. 52 , 53 Furthermore, the onset of the effects of mFV occurs as soon as 60 minutes after the end of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most common malignancy affecting the female population and the second most common cause of death from malignant tumors in this group. Increasing morbidity is observed all over the world [3,4]. The incidence of breast cancer is estimated to increase 3 times by 2050 compared to 2013 [4].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of treatments of a systemic nature increases the life expectancy of women diagnosed with breast cancer but may leave behind chronic side effects in the form of functional deficits and mental health problems [3,5,6,7]. Deterioration of both physical and mental functioning leads to significant changes in a woman's family, social, and professional life and is a major cause of reduced quality of life [5,7,8].…”
Section: Introductionmentioning
confidence: 99%